ETIKA AKUNTAN INDONESIA BERBASIS BUDAYA JAWA, BATAK, DAN BALI: PENDEKATAN ANTROPOLOGIS - Putri, Ike Nurkusuma; Kamayanti, Ari (Jurnal Ilmiah Mahasiswa FEB, 2013)
This  research is  to  interpret  the  Indonesian accountant  ethical values  of different culture through anthropological approach. The results show  that the local cultural ethics can support or weaken the general principle of the code of accountant ethics. The general principles of the code of accountant ethics IAI which has been adapted to Javanese Ethics, Batak Ethics and Bali Ethics can be proposed to complement the general principles of the accountants ethics that already exist. The ethics include etika penurut  (spiritual),  etika eling lan waspada,  etika sungkan  (respect),  etika mangan ora mangan sing penting kumpul (simplicity), etika disiplin, etika menjaga keseimbangan, etika toleransi (religious life), etika mempercayai karma. Keywords : Code of accountant ethics IAI, Culture, Antropological approach